2019
DOI: 10.1002/fsn3.949
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding hyperlipidemia rats with symbiotic oat‐based frozen yogurt on serum triglycerides and cholesterol

Abstract: Ice cream is one of the most popular dairy foods in the world. But it has long been recognized as a high‐calorie food and may not be suitable for certain segments of the population. Oat‐based food products are considered as functional foods due to its rich β‐glucan. A symbiotic oat‐based frozen yogurt ( SOFY ) containing fermented oat, probiotics, and inulin (prebiotic) was developed, and its effects on serum lipids in rats were evaluated. The new product had 4.10% protein, 8.50% fat, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The amount of visceral fat is usually related to changes in serum lipids‐related metabolic indicators. Previous studies have revealed that yogurt and probiotics can improve blood lipid‐related indicators, usually manifested as a decrease in serum TG, TC and LDL levels (Yang et al, 2019). In our study, we also confirmed that both NDY and NYC reduced serum levels of TG, TC, LDL, and GLU.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of visceral fat is usually related to changes in serum lipids‐related metabolic indicators. Previous studies have revealed that yogurt and probiotics can improve blood lipid‐related indicators, usually manifested as a decrease in serum TG, TC and LDL levels (Yang et al, 2019). In our study, we also confirmed that both NDY and NYC reduced serum levels of TG, TC, LDL, and GLU.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Moroti et al [14] which aimed to evaluate the effect of consuming a synbiotic shake contained Lactobacillus acidophilus, Bifidobacterium bifidum and FOS in the elderly showed that consumption of 200 mL synbiotic shake for 4 weeks showed a significant increase in HDL levels from 43.33 mg/dL to 58.56 mg/dL, the decrease in total cholesterol, and the insignificant changes in triglyceride. Another study by Yang et al [21] showed that synbiotics administration contained Bifidobacterium, Lactobacillus acidophilus, and inulin to hyperlipidemic rats for 8 weeks was able to reduce triglyceride, cholesterol, and LDL levels significantly. Research conducted on experimental pigs by administered synbiotics contained Lactobacillus acidophilus, FOS, inulin, and mannitol for 8 weeks showed a significant reduction in serum triglyceride, cholesterol, and LDL as well as increased HDL levels in hypercholesterolemic pigs [22].…”
Section: Effect Of Synbiotic Shake Administration On Lipid Profilementioning
confidence: 99%
“…Furthermore, a study found that serum blood glucose, blood lipid and atherogenic index were decreased in the study of testing the newly developed oat-beans cookies, and the functional snack bar about oat also has antioxidant, thermal stability and long shelf life advantages . On the other hand, some researchers used these oat functional foods during their experiments in order to hold the good dining experience of subjects, and these results show oat had a good effect on lowering blood lipid and blood pressure. Thus, the research and development of oat-based functional foods may have enormous potential.…”
Section: Oat As Functional Foods and The Safetymentioning
confidence: 99%